Perlindungan Hukum Hak Atas Tanah Masyarakat Terhadap Pembangunan Berkelanjutan Di Kota Kupang - Engelbertus Tobu; Benediktus Peter Lay; Antonia Immaculata Putri Seran (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The dynamics of development result in the need for land increasing while on the other hand the supply of land is very limited, so that additions to one need will reduce the supply of land for other needs. Land acquisition is the activity of providing land by providing proper and fair compensation to the rightful party. The issuance of Law No. 2 of 2012 concerning land acquisition (land acquisition law) as a legal basis for the government that will carry out development activities that require land is expected to guarantee legal certainty in land acquisition and fulfill a sense of justice for those affected by land acquisition. This study aims to analyze the provision of compensation for land acquisition in the case of the Tomboy family. The type of research used is Juridical Empirical using the Empirical Legal Approach Method. The form of compensation in land acquisition is money, replacement land, resettlement, share ownership or other forms agreed by both parties.